1981
DOI: 10.2151/jmsj1965.59.3_373
|View full text |Cite
|
Sign up to set email alerts
|

On the Stagnant Zone Upstream of an Obstacle within a Stably Stratified Flow in the Atmosphere

Abstract: Stably stratified airflows over a hill or mountain are studied by a wind tunnel and also by a theoretical model with special forcus on the upstream stagnant zone. The wind tunnel experiment shows that a stagnant zone is formed upstream of an obstacle when the Froude number is less than some critical value. The critical Froude number is found to vary with the obstacle height. In the stagnant zone, the airflow is negligible or reverse and the thickness of the zone decreases gradually with the distance from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…He used the wind-tunnel test-section depth in defining his Froude number, but concluded that a critical Froude number based on the barrier height should be adopted. His data (Kitabayashi 1981 ; figure 19) can be used to support the argument for a critical Froude number for upstream blocking, based on hill height, of F x 1.0.…”
Section: -2mentioning
confidence: 88%
See 1 more Smart Citation
“…He used the wind-tunnel test-section depth in defining his Froude number, but concluded that a critical Froude number based on the barrier height should be adopted. His data (Kitabayashi 1981 ; figure 19) can be used to support the argument for a critical Froude number for upstream blocking, based on hill height, of F x 1.0.…”
Section: -2mentioning
confidence: 88%
“…However, the approach wind profile was not uniform and the density profile was not linear, so the Froude numbers he calculated are not directly comparable to those of more idealized laboratory studies. Kitabayashi (1981) continued his studies of stratified flow over two-dimensional objects by analysing the flow over thin, vertical barriers. He used the wind-tunnel test-section depth in defining his Froude number, but concluded that a critical Froude number based on the barrier height should be adopted.…”
Section: -2mentioning
confidence: 99%